Analysis of the Impact of Taxation on Affiliate Earnings in the Shopee Affiliate Program - Awalia Fitriyani; Sukemi Kamto Sudibyo; Edy Siswanto (CV. Publikasi Indonesia, 2026)
This research aims to analyze the effect of tax knowledge and tax regulation implementation on the net income of affiliators in the Shopee Affiliate Program, with affiliator motivation examined as a mediating variable. Income earned through affiliate marketing activities is classified as an object of Income Tax (PPh) Article 21 in Indonesia, yet many affiliators still lack adequate understanding of their tax obligations, creating a gap this study seeks to address. This quantitative associative-causal study used an online five-point Likert-scale questionnaire distributed via Google Form to 100 Shopee affiliators with active NPWP, minimum three months of activity, and prior taxable commission receipts. Data were analyzed using SEM-PLS, evaluating both measurement and structural models. The results show that tax knowledge and tax regulation implementation each have a positive and significant effect on affiliator net income. Tax regulation implementation also has a positive and significant effect on affiliator motivation, whereas tax knowledge does not significantly affect motivation. Motivation itself has a positive and significant effect on income and is shown to mediate the effect of tax regulation implementation on income, but does not mediate the effect of tax knowledge on income. These findings indicate that clear, well-socialized tax regulation together with strengthened affiliator motivation are key factors in improving affiliator income, while tax knowledge plays a more direct, technical role in income management rather than a motivational one.